Origins of Type Ibn SNe 2006jc/2015G in interacting binaries and implications for pre-SN eruptions. Issue 4 (6th December 2019) - Sun, Ning-Chen; Maund, Jusytn R; Hirai, Ryosuke; Crowther, Paul A; Podsiadlowski, Philipp
ABSTRACT: Type Ibn supernovae (SNe Ibn) are intriguing stellar explosions whose spectra exhibit narrow helium lines with little hydrogen. They trace the presence of circumstellar material (CSM) formed via pre-SN eruptions of their stripped-envelope progenitors. Early work has generally assumed that SNe Ibn come from massive Wolf–Rayet (WR) stars via single-star evolution. In this paper, we report ultraviolet (UV) and optical observations of two nearby Type Ibn SNe 2006jc and 2015G conducted with the Hubble Space Telescope ( HST ) at late times. A point source is detected at the position of SN 2006jc, and we confirm the conclusion of Maund et al. that it is the progenitor's binary companion. Its position on the Hertzsprung–Russell (HR) diagram corresponds to a star that has evolved off the main sequence (MS); further analysis implies a low initial mass for the companion star ( M 2 ≤ 12.3^+2.3_-1.5 M⊙ ) and a secondary-to-primary initial mass ratio very close to unity ( q = M 2 / M 1 ∼ 1); the SN progenitor's hydrogen envelope had been stripped through binary interaction. We do not detect the binary companion of SN 2015G. For both SNe, the surrounding stellar populations have relatively old ages and argue against any massive WR stars as their progenitors. These results suggest that SNe Ibn may have lower mass origins in interacting binaries. As a result, they also provide evidence that the giant eruptions commonly seen in massive luminous blue variables (LBVs) can also occur in much lower mass, stripped-envelope stars just before core collapse.